Assessing undergraduate students' performance in simultaneous interpreting: A qualitative analysis of accuracy, fluency, and language quality - Alrawashdeh, Haneen; Bani Baker, Muna; Almahasees, Zakaryia; Abd Allah Meqdad , Saad; Haider, Ahmad S; Gwasmeh, Muneir; Darwish, Noor; Saed, Hadeel; Al-Momani, Abdullah Mohammed (Research Journal in Advanced Humanities, 2026)
While the subject of simultaneous interpreting (SI) has attracted substantial interest in cognitive and professional literature, much less research effort has been devoted to the examination of the quality of English-Arabic SI performance of undergraduate trainee interpreters using systematic quality assessment frameworks. This study seeks to address this gap by investigating the performance of fourth-year undergraduate translation students at Yarmouk University through an examination of the strategies they use to cope with the linguistic and cognitive complexities of English-Arabic simultaneous interpreting. It uses a corpus of recordings of interpreting performances conducted in an interpreting laboratory, specifically set up for this purpose, and applies qualitative content analysis to identify the quality problems of trainee interpreters and the strategies they adopt regarding accuracy, fluency, and language quality. The results show that the most frequent strategy is that of omission, indicating that novice interpreters tend to sacrifice completeness of the interpretation to message continuity when the cognitive complexity surpasses their cognitive resources. Substitution and simplification are commonly used as strategies to maintain the communicative intention when the vocabulary retrieval problem emerges, while addition is used from time to time to clarify some implicit information in the source text. Hesitation, repetition, and self-correction constitute fluency-coping strategies, while the widespread problem of literal transfer shows that producing natural Arabic target text remains problematic. Such findings demonstrate the applicability of the MQM framework for interpreter evaluation in an educational context and contribute to the empirical knowledge about the performance problems novice interpreters face in English-Arabic simultaneous interpreting.